A community of Europeans? : transnational identities and public spheres - Risse, Thomas, 1955- (Cornell paperbacks., 2010)
In this work, a thoughtful observer of the on-going project of European integration evaluates the state of the art about European identity and European public spheres. The author argues that integration has had profound and long-term effects on the citizens of EU countries.